Analysis Of Indicators Of Investment In Government Educational Services (Education Sector) In The Kurdistan Region – Iraq For The Duration2003-2018 - Rahida taher Azeez; Yaseen othman abdulaah (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
The study of the analysis of investment indicators in government educational services in the education sector is one of the important issues at the national level in terms of showing the role the government plays through the state budget allocations, which may outweigh other investment aspects. The research aims to diagnose a. This research aims to diagnose the role of investment spending in developing educational services (education sector) in the Kurdistan Region - Iraq. The research assumed that investment spending has a significant role in developing educational services in the Kurdistan Region - Iraq. The educational investment spending has a positive impact on developing the number of government schools, the number of teachers in the education sector, and the number of students in the education sector. As the research found results, the most important of which is that despite a decrease in educational expenditures for the education sector in the region for some years, the figures indicate a general trend for the increase in total educational expenditures during the research period. 2012, 2013 and 2017. This shows the average annual rate of change, not the total period, which reached (40.82%). And the rates of development in the three governorates of the teaching staff in it seem to us that Erbil, the capital, has been characterized by the fact that the rate of development in the teaching staff for the three stages was less than the general region, while the rate of development in the teaching staff of the governorates of Sulaymaniyah and Dohuk was higher than the whole region. The reason for this seems to be that the governorates of Sulaymaniyah and Dohuk have many emerging rural areas, which need increasing numbers of teaching staff.